Toward a role model. (15th October 2013) - Sharan, Roded
Abstract : With ever‐growing amounts of 'omics data, the challenge is to develop an automatic modelling pipeline that receives as input large‐scale data pertaining to the system of interest and outputs a complete, logical model that maximizes the fit to the given data.